2018
DOI: 10.1021/acs.langmuir.8b00350
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Attachment, Aggregation, and Alignment on Subcellular Nanogratings

Abstract: Recent investigations on the interactions of bacteria with micro/nanostructures have revealed a wide range of prokaryotic responses that were previously unknown. Despite these advances, however, it remains unclear how collective bacterial behavior on a surface would be influenced by the presence of anisotropic nanostructures with subcellular dimensions. To clarify this, the attachment, aggregation, and alignment of Pseudomonas aeruginosa on orderly subcellular nanogratings with systematically varied geometries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…The features on these surfaces seemed able to direct cell patterning independent of the expression of appendages by the cells (Hochbaum and Aizenberg, 2010). The interstitial space between surface features (Epstein et al, 2011) and the depth of the features (Lai, 2018) were both found to be critical for bacterial cell patterning. For example, aggregation of P. aeruginosa cells on Si nanogratings was reduced to 20% of that on flat controls, because the cells were entrapped to the bottom of the Si nanogratings deeper than 500 nm, and consequently became unavailable for forming cell clusters (Lai, 2018).…”
Section: Effect Of Topographical Scale On Bacterial Attachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The features on these surfaces seemed able to direct cell patterning independent of the expression of appendages by the cells (Hochbaum and Aizenberg, 2010). The interstitial space between surface features (Epstein et al, 2011) and the depth of the features (Lai, 2018) were both found to be critical for bacterial cell patterning. For example, aggregation of P. aeruginosa cells on Si nanogratings was reduced to 20% of that on flat controls, because the cells were entrapped to the bottom of the Si nanogratings deeper than 500 nm, and consequently became unavailable for forming cell clusters (Lai, 2018).…”
Section: Effect Of Topographical Scale On Bacterial Attachmentmentioning
confidence: 99%
“…The interstitial space between surface features (Epstein et al, 2011) and the depth of the features (Lai, 2018) were both found to be critical for bacterial cell patterning. For example, aggregation of P. aeruginosa cells on Si nanogratings was reduced to 20% of that on flat controls, because the cells were entrapped to the bottom of the Si nanogratings deeper than 500 nm, and consequently became unavailable for forming cell clusters (Lai, 2018). The patterning and ordering of early colonizers can interfere with natural biofilm development and organization (Hochbaum and Aizenberg, 2010), as some bacteria rely on contact-dependent signaling cascades to achieve cooperative communal functions (Blango and Mulvey, 2009).…”
Section: Effect Of Topographical Scale On Bacterial Attachmentmentioning
confidence: 99%
“…Hochbaum et al 4 found that P. aeruginosa PA14 tended to maximum their contact area with the surface, forming a spontaneous cell alignment between periodic nanopillars with a post pitch of 2.2, 0.9 and 0.7 mm. Subsequent work showed similar behaviour as P. aeruginosa aligned within subcellular-nanogratings, 13 Escherichia coli orientated towards surface line patterns, 14 and Pseudomonas fluorescens were trapped preferentially in surface trenches. 15 As such, topographical features with micrometre or submicrometer length scales (i.e., comparable with the length scale of the bacteria themselves) can influence the arrangement of adhered cells during the early stage of biofilm development.…”
Section: Introductionmentioning
confidence: 78%
“…Our investigations above indicated that cell alignment may be a general phenomenon, occurring in examples of wild-type bacteria and in the absence of flagella or pili, which was also consistent with the findings in other studies. 4,13 Overall, the investigation above showed that the surface topography at the micro-and nanoscale that is comparable to the bacterial size, can affect bacterial alignment and attachment. It is likely that cells try to maximize contact area with the surface topography, presumably to achieve a stronger and more stable attachment, which results in a specific alignment behaviour of the attached cells.…”
Section: Bacterial Nanotubes Aid In the Cell-cell Connections On Nanomentioning
confidence: 86%
See 1 more Smart Citation